Retrospective, multicenter study of surgical treatment for carotid body tumors with or without preoperative embolization - Han, Tonglei; Pu, Jiaxi; Tang, Hanfei; Yang, Shaofei; Dong, Dandan; Lu, Minhao; Wei, Xiaolong; Yang, Guanghua; Zhao, Bin; Guo, Daqiao; Tang, Xiao; Zhao, Zhiqing (Frontiers in Oncology, 2023)
Background: Carotid body tumor (CBT) is the most common head and neck paragangliomas. Whether preoperative embolization is benefit for CBT patients who will receive surgical resection is still controversial. Methods: In this multi-center retrospective study, we collected data of patients with CBT who received surgical treatment without (group A) or with preoperative embolization (group B) from 2011 to 2019. The primary outcome was the rate of death or stroke after three years follow up. The secondary outcomes of the study were length of operation (LOO), intraoperative blood loss (IBL), length of stay (LOS), the rate of recurrence and the rate of cranial nerve (CN) injuries. Descriptive statistics were used to analyze the demographics, clinical characteristics, complications, and follow-up results of the patients. Results: Between January 2011 and October 2019, 261 consecutive patients (107 male and 154 female) entered analysis. After 3 years follow up, no patient dead in both groups. Only 3 patients stroke were detected: 2/226 (0.9%) in group A vs. 1/35 (2.9%) in group B (p = .308). The LOO in group A was 132.6 ± 64.6 min compared with 152.9 ± 40.4 min in group B (p = .072). IBL in group A was 375.4 ± 497.8 ml compared with 448.0 ± 270.8 ml in group B (p = .400). LOS in group A was 8.3 ± 2.0 days compared with 7.4 ± 1.7 days in group B (p = .016). Seventy-two CN injuries were detected: 65/226 (28.8%) in group A vs. 7/35 (20.0%) in group B (p = .281). There were 65 temporary CN injuries (59 in group A vs. 6 in group B) (p = .254) and 7 permanent CN injuries (6 in group A vs. 1 in group B) (p = .945). Three most frequently injured cranial nerves were pharyngeal branch and superior laryngeal nerve (12.3%), recurrent laryngeal nerve (7.7%) and vagus nerve (7.3%). Conclusion: There was insufficient evidence to support the efficacy of preoperative embolization, CBT resection alone had a low rate of death or stoke, recurrence and CN injuries. And CBT resection alone did not increase LOO and IBL.